Parasites of Pampas deer (Ozotoceros bezoarticus L. 1758) in sympatry with livestock in Uruguayan agroecosystems - Castro, Mayra (2021)
In the recent past, the Pampas deer (Ozotoceros bezoarticus Linnaeus, 1758) has been one of the most characteristic species in Uruguayan grasslands. Currently, the Pampas deer populations are small, endangered and highly isolated, remaining in cattle ranches. The aim of this study is to describe the gastrointestinal parasites of a Pampas deer (O. b. arerunguaensis) population that share paddocks and grazing areas with bovine and ovine populations in each season along one year, using coproparasitological techniques. Morphological analysis of eggs and larvae and the quantification of eggs per gram of feces were performed on faecal samples from three ruminant species (119 of deer, 144 of cattle and 85 of sheep) that share three paddocks. The parasitic taxonomic identification was made from infesting larvae obtained by the egg stool culture. Some genera of parasites were shared between domestic ruminants and Pampas deers, in different seasons. The greatest parasite generic richness was found in winter from calves and ovines, being the largest record also observed in the Pampas deers from the paddock C. The epg counting in samples of Pampas deer from the three paddocks showed a similar seasonal behavior throughout the year (p =0.89). We diagnosed the presence of Haemonchus, Oesophagostomum, Ostertagia, and Trichostrongylus in Pampas deer. Finally, it is recommended to maintain parasitic chemical restraint measures to avoid the transmission of species from domestic ruminants to wild fauna found in sympatry.